Lower bound on deformation for dynamically loaded rigid-plastic structures - The, Vu Van; Tinh, Tran Ba (Vietnam Journal of Mechanics, 1992)
In this work comparisons are made between lower bound obtaining in [3], stronger and lower bound by The-Sawczuk. Finally the optimal problem is considered, namely that it must be chosen fi1(t) fi2 (xk), for which a lower bound displacement is maximized.